CT with image reformation for noninvasive screening of the carotid bifurcation: early experience. - Brant-Zawadzki, M; Jeffrey, R B (American Journal of Neuroradiology, 1982)
Twenty-two cervical carotid artery bifurcations were evaluated in 11 patients using a high-resolution computed tomographic (CT) technique with image reformation permitting display of the bifurcation anatomy. Arteriography was also done in eight of the patients, two of whom subsequently underwent carotid endarterectomy. The CT study showed patency of the proximal internal carotid artery in every case and depicted significant stenosis of four vessels. Thrombus within a large ulcer was seen in one vessel on CT, but another shallow ulcer found on angiography was missed. Although the data are limited, this preliminary experience suggests a possible role for this technique in carotid bifurcation screening and indicates further investigation may be worthwhile.